Where the Everyday Begins : A Study of Environment and Everyday Life - Morrow, James (Sozialtheorie, 2017)
Where the Everyday Begins is a study of environment and everyday life. It uses innovative research methods to bear witness to the ways by which environment defines everyday life. And its lively narrative pulls together a multitude of observations that reveal incredible details about the social and material ecologies that bind the world.